Effect of diminazene aceturate on the infectivity and transmissibility of drug-resistant Trypanosoma congolense in Glossina morsitans centralis - Diack, A.; Moloo, S.K.; Peregrine, A.S. (Elsevier, 1997)
To determine the duration after treatment of cattle with diminazene aceturate that the drug influences the tsetse infectivity and transmissibility of a drug-resistant Trypanosoma congolense, six Boran cattle were infected with T. congolense IL 3338 via the bites of Glossina morsitans centralis. At the first peak of parasitaemia, different groups of 120 teneral G. m. centralis were fed on one occasion on each animal, 1 h before treatment with diminazene aceturate at a dose of 3.5 mg kg-1 body weight. Thereafter, on Days 1, 2, 3, 7, 14 and 21 after treatment, six different groups of 120 teneral G. m centralis were similarly fed on each animal. After 28 days maintenance on uninfected goats, all the flies were probed onto slides at 37 degree centigrade to identify those extruding metacyclic trypanosomes. Flies with mature infections from each group were then fed on one occasion on individual mice to determine the transmissibility index. After dissection of flies on Day 30 after their feed on the cattle, the mean mature ((+ or -)SE) infection rates in the seven groups of flies were 32.1 (+ or -) 2.2, 1.0 (+ or -) 0.7, 0.4 (+ or -) 0.4, 0.5 (+ or -) 0.3, 20.0 (+ or -) 1.7, 33.3 (+ or -) 2.2 and 23.4 (+ or -) 2.0 percent for flies fed on Days 0, 1, 2, 3, 7, 14 and 21 after treatment with diminazene, respectively. The transmissibility rates for the seven groups ranged from 94 to 100 percent. Thus, when cattle were infected with a diminazene-resistant T/ congolense, treatment with diminazene aceturate caused a substantial reduction in the ability of the trypanosomes to establish mature infections in tsetse for at least the first 7 days after treatment. In contrast, no significant effect on the transmissibility of the parasites to mice was observed at different intervals after treatment.